THE PROBLEM OF PROVING THE INVOLVEMENT OF STATE CIVIL APPARATUS IN REGIONAL HEAD ELECTIONS IN A STRUCTURED, SYSTEMATIC AND MASSIVE MANNER IN DISPUTES IN THE CONSTITUTIONAL COURT - Mora, Diana (Inspiring Law Journal, 2025)
The election of regional heads is a real manifestation of the sovereignty of the people, as stated in Article 18 paragraph (4) of the 1945 Constitution, stating